Exploring the 10Li structure by the d(9Li, p)10Li transfer reaction. (March 2015) - Cavallaro, M; De Napoli, M; Cappuzzello, F; Agodi, C; Bondì, M; Carbone, D; Cunsolo, A; Davids, B; Davinson, T; Foti, A; Galinski, N; Kanungo, R; et al.
Abstract: The 9 Li + 2 H reaction has been investigated at 11 AMeV incident energy at the ISAC II facility (TRIUMF). In the present paper we focus on the one-neutron transfer channel, which potentially holds spectroscopic information on the unbound nucleus 10 Li. The TUDA setup has been used in order to detect and identify the outgoing 9 Li at forward angles and the recoil protons at backward angles. This setup allows to study the 10 Li emitted in the crucial region at forward angles in the center of mass.